IFCS-2004 Chicago - kilka refleksji - Sokołowski, Andrzej; Jajuga, Krzysztof (IFCS-2004 Chicago - Some Impressions, 2005)
The paper presents some facts and remarks on the world IFCS conference, which took place in Chicago. First of all, some facts on IFCS and SKAD - Polish member society are presented. Then we provide the analysis of the contents of the papers presented during conference.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 19-25